Ah! Simeon! - Yap, Januar (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
Simeon Dumdum Jr. left the seminary of his youth to set out a life as a poet. Though in the legal profession for most of his career, he is defined by eighteen books of poetry and prose as a true man of letters. His poetry has the specificities of the human and humane bearing witness between history at large and moments in particular. He has written 129 bird poems within the duration of a chemotherapy, versified grief over a loved one’s death, played tanka with the wife, and even wrote judicial decisions like literature. If attention is a measure of a poet’s care of the world, Dumdum’s gaze freezes the fleeting. A poet can never be cruel, he says. The humanizing effect of writing verse becomes an invocation to the divine.